Alterations in the Synthesis of IL-1β, TNF-α, IL-6, and Their Downstream Targets RANKL and OPG by Mouse Calvarial Osteoblasts In vitro: Inhibition of Bone Resorption by Cyclic Mechanical Strain - García-López, Salvador; Villanueva, Rosina E.; Meikle, Murray C. (Frontiers in Endocrinology, 2013)
Mechanical strain is an important determinant of bone mass and architecture, and the aim of this investigation was to further understand the role of the cell-cell signalling molecules, IL1-β, TNF-α and IL-6 in the mechanobiology of bone. Mouse calvarial osteoblasts in monolayer culture were subjected to a cyclic out-of-plane deformation of 0.69% for 6 s, every 90 s for 2‒48 h, and the levels of each cytokine plus their downstream targets RANKL and OPG measured in culture supernatants by ELISAs. Mouse osteoblasts constitutively synthesized IL-1β, TNF-α and IL-6, the production of which was significantly up-regulated in all three by cyclic mechanical strain. RANKL and OPG were also constitutively synthesized; mechanical deformation however, resulted in a down-regulation of RANKL and an up-regulation OPG synthesis. We next tested whether the immunoreactive RANKL and OPG were biologically active in an isolated osteoclast resorption pit assay - this showed that culture supernatants from mechanically-deformed cells significantly inhibited osteoclast-mediated resorptive activity across the 48 h time-course. These findings are counterintuitive, because IL-1β, TNF-α and IL-6 have well-established reputations as bone resorptive agents. Nevertheless, they are pleiotropic molecules with multiple biological activities, underlining the complexity of the biological response of osteoblasts to mechanical deformation, and the need to understand cell-cell signalling in terms of cytokine networks. It is also important to recognize that osteoblasts cultured in vitro are deprived of the mechanical stimuli to which they are exposed in vivo - in other words, the cells are in a physiological default state that in the intact skeleton leads to decreased bone strains below the critical threshold required to maintain normal bone structure.